Macroplastic Characteristics and Assessment of the Plastic Abundance Index (PAI) of Beach Sediments in Prigi Bay, East Java, Indonesia - Adinda P.A. Nevandhra; Seftiawan S. Rijal; Syarifah H.J. Sari; Defri Yona (Applied Environmental Research)
Macroplastics, defined as plastic debris ranging from 2.5 to 100 cm, pose significant threats to aquatic ecosystems, as they can breakdown into smaller particles. These materials are widely dispersed across marine environments, including coastal areas. This study aimed to compare and assess the abundance of macroplastics in the foreshore and backshore zones of four beaches around Prigi Bay, East Java, Indonesia, via the plastic abundance index (PAI). Macro-plastics were collected via a 5×5 m quadrat transect method. The results revealed that single-use plastics, particularly packaging and sachets, dominated both zones, accounting for 86% and 91% of the total number of plastic items in the foreshore and backshore waste, respectively. The average abundance in the foreshore area was 0.71±0.21 items m-² and 2.47±0.78 g m-², whereas that in the backshore area was significantly greater, at 1.59±0.40 items m-² and 3.32 ±2.39 g m-². According to the PAI classification, the foreshore exhibited 'High Abundance' (PAI 4.1–8), whereas the backshore was categorized as 'Very High Abundance' (PAI > 8). These differences were attributed to human activity and environmental factors: the backshore, which is frequently used by tourists and less affected by wave action, accumulated a larger number of small, lightweight plastics, whereas the foreshore, which is exposed to tidal movements, contained fewer but larger and heavier macroplastics. The findings of this study underscore the importance of implementing targeted waste management strategies by identifying zones with the highest plastic accumulation and prioritizing the reduction of single-use plastics, especially packaging and sachets. These results can inform localized cleanup efforts, the placement of waste bins, and public education programs focused on areas with intense tourist activity, thereby mitigating macroplastic pollution and its environmental impact on both foreshore and backshore zones.